White adipose tissue in type 2 diabetes and the effect of antidiabetic drugs - Yixuan Zhao; Rensong Yue (Diabetology & Metabolic Syndrome)
Abstract White adipose tissue (WAT) is highly flexible and was previously considered a passive location for energy storage. Its endocrine function has been established for several years, earning it the title of an “endocrine organ” due to its ability to secrete many adipokines that regulate metabolism. WAT is one of the core tissues that influence insulin sensitivity. Its dysfunction enhances insulin resistance and type 2 diabetes (T2D) progression. However, T2D may cause WAT dysfunction, including changes in distribution, metabolism, adipocyte hypertrophy, inflammation, aging, and adipokines and free fatty acid levels, which may exacerbate insulin resistance. This review used PubMed to search WAT dysfunction in T2D and the effects of these changes on insulin resistance. Additionally, we described and discussed the effects of antidiabetic drugs, including insulin therapy, sulfonylureas, metformin, glucose-like peptide-1 receptor agonists, thiazolidinediones, and sodium-dependent glucose transporters-2 inhibitors, on WAT parameters under T2D conditions.